Intermediate Results of Prospective Observational Study: The 2-year Experience of Ibrutinib Therapy in Relapsed/Refractory Mantle Cell Lymphoma in Clinical Practice - VI Vorob’ev; VA Zherebtsova; EI Dubrovin; LA Bychenkova; YuB Kochkareva; LA Mukha; VL Ivanova; NK Khuazheva; VV Ptushkin (Клиническая онкогематология)

(untitled)
Aim. To assess efficacy and toxicity of ibrutinib monotherapy in patients with relapsed/refractory mantle cell lymphoma (MCL).